Investigating the empirical relation and importance of perceived usefulness, perceived ease of use and intention to use online information resources for evidence based medicine - Chandio, Fida Hussain; Anwar, Fozia; Zeki, Akram M.; Rizvi, seema (IEEE, 2015)
This study explores the empirical relationship and importance of perceived usefulness, perceived ease of use and intention to use online information resources for Evidencebased Medicine (EBM). Although a significant literature is available that investigates the effect of various factors on intention to use digital information sources to practice EBM in developed countries. However, literature is a lacking in exploring the intention to practice EBM by physicians in developing countries like Pakistan. This is the motivation behind this study. This research is a cross sectional quantitative survey study (N=352). Based on related literature a questionnaire was developed. Selected participant sample of the survey is those physicians, who were in clinical practice and were having the knowledge of EBM. Structural equation modelling technique (SEM) with the Analysis of Moment Structures software (AMOS) is used for data analysis. The findings showed the significance and causal linkage between perceived usefulness, perceived ease of use and intention to use online information resources for EBM. Perceived usefulness is found as a strong predictor in acceptance and behavioral intention as compared to the perceived ease of use